2019
DOI: 10.3889/oamjms.2019.379
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Phacoemulsification Cataract Surgery Outcomes After Penetrating Keratoplasty

Abstract: BACKGROUND: Cataract is one of the reasons which causes impaired visual acuity (VA) of the eyes after penetrating keratoplasy (PK), which can be treated by cataract surgery after PK or triple procedure. Cataract surgery after PK has advantages that parameters of the eyes such as axial length, anterior chamber depth (ACD) as well as corneal curvature are stabilized after removing all sutures postoperatively, and intraocular lens (IOL) power can be calculated correctly. Therefore, postoperative VA will be improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…In addition, other studies observed a decline in visual acuity in the majority of operated patients (89.9%) with visual acuity of ≤ 20/200 and moderate cataracts. This decline could be attributed to an immunologic graft reaction and edematous cornea (Cung et al, 2019), as well as automated refraction and corneal swelling (De Juan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other studies observed a decline in visual acuity in the majority of operated patients (89.9%) with visual acuity of ≤ 20/200 and moderate cataracts. This decline could be attributed to an immunologic graft reaction and edematous cornea (Cung et al, 2019), as well as automated refraction and corneal swelling (De Juan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also used the SRK-T formula and corneal topography data and targeted a myopic postoperative spherical equivalent. 18,19 Preoperatively, we used the SRK-T formula with the mean keratometry provided by the specular corneal topographer and either B-scan or IOLMaster axial length (according to the measurement precision) to calculate the IOL power. A study evaluating IOL power calculation for the triple procedure (PK combined with cataract surgery) did not find significant differences in the mean absolute postoperative refractive error between the SRK-T, Holladay 1, and Hoffer Q formulas.…”
Section: Discussionmentioning
confidence: 99%
“…При исследовании параметров роговицы большинством авторов рекомендуется заблаговременно снять роговичные швы, фиксирующие трансплантат, так как значения кератометрии, включающиеся в расчет ИОЛ, могут значительно измениться при интраоперационном или послеоперационном удалении шовного материала; при этом изменение рефракции в результате снятия шва может значительно снизить некоррегированную остроту зрения, полученную после имплантации ИОЛ. Поэтому, если возможно, следует дождаться полного снятия швов и последующей стабилизации кривизны роговицы после CКП c целью обеспечения стабильного рефракционного результата[7,14,15]. зависящих от оператора, которых нет при оптическом методе[17,18].…”
unclassified